DINAMIKA PETANI DALAM BERAGRIBISNIS SALAK (Kasus di Kabupaten Karangasem Provinsi Bali) - I Gede Setiawan; Adi Putra; Pang S. Asngari; Prabowo Tjitropranoto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
Bali salak is germ plasm of Balinese salak which has good potency for economic development, but not been handled to the seriously agribusiness system. The objectives of this research: (1) to describe internal factors of salak agribusiness farmers, (2) ) to describe external factors of salak agribusiness farmer, and (3) to analyze the relationship among internal and external factors and farmer’s dynamic in agribusiness of salak. This research used descriptive correlation method. The result of this research showed that factors, which influence the farmer’s dynamic in salak agribusiness, were: (1) internal factors are in low and middle category, (2) external factors are in middle and high category, and (3) internal and external factors had relationship with the farmer’s dynamic in agribusiness of salak.